The correlation between cranial and post-cranial skeletal elements for resolving and reconstruction of comingled skeletal remains in victim identification - Marais, Johan Christian (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.